ВЫЯВЛЕНИЕ ОСОБЕННОСТЕЙ УПРАВЛЕНИЯ ИННОВАЦИОННЫМИ ПРОЦЕССАМИ В РЕГИОНАЛЬНЫХ ВУЗАХ РЕСПУБЛИКИ УЗБЕКИСТАН - Доспанов, Р. (SCIENCE and SOCIETY, 2025)
Our article deals with management of innovation processes in regional universities of Uzbekistan in the context of globalization and the transition to a knowledge economy. The article emphasizes the need for cooperation between universities and industrial enterprises to train highly qualified personnel capable of supporting the innovative development of regions.
Keywords: Innovative processes; regional universities; quality management; higher education; personnel training; knowledge econ- omy; cooperation between universities and enterprises; innovation policy; competitiveness; information technology; regional develop- ment; systems approach